2007
DOI: 10.1097/ta.0b013e318068d72b
|View full text |Cite
|
Sign up to set email alerts
|

Hypovolemic Shock Evaluated by Sonographic Measurement of the Inferior Vena Cava During Resuscitation in Trauma Patients

Abstract: In trauma patients, inadequate dilatation of the IVC by fluid resuscitation, might indicate insufficient circulating blood volume despite normalization of blood pressure. In this small study, IVC diameter appeared a better predictor of recurrence of shock than blood pressure, heart rate, or arterial base excess. A larger prospective study is called for to clearly establish the sensitivity and specificity of this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(73 citation statements)
references
References 13 publications
1
67
0
5
Order By: Relevance
“…In particular, the minimum diameter decreased dramatically on the CT examination while hemodynamically unstable, which suggests that the IVC changed shape as well during hemodynamic instability, from an approximately round shape to a more elliptic shape. Decreasing diameters of the IVC during hemodynamic instability and/or hypovolemic shock has been described before, [36][37][38][39] and some have opted that the IVC diameter is more sensitive than the blood pressure alone for identifying a hypovolemic state in trauma patients. 36 Limitations.…”
Section: Discussionmentioning
confidence: 96%
“…In particular, the minimum diameter decreased dramatically on the CT examination while hemodynamically unstable, which suggests that the IVC changed shape as well during hemodynamic instability, from an approximately round shape to a more elliptic shape. Decreasing diameters of the IVC during hemodynamic instability and/or hypovolemic shock has been described before, [36][37][38][39] and some have opted that the IVC diameter is more sensitive than the blood pressure alone for identifying a hypovolemic state in trauma patients. 36 Limitations.…”
Section: Discussionmentioning
confidence: 96%
“…Finnerty et al (36) showed a reversible 15% decrease in plasma volume following a 15 min infusion of levarterenol, an a-blocking drug, in ten human volunteers. Such changes in blood volume are of little clinical relevance (37). Furthermore and importantly, as early as 1977, when comparing two personal historical studies of patients undergoing adrenalectomy for pheochromocytoma, Desmont & Marty (16) reported that administering fluid only intraoperatively, whenever necessary, was as efficient as preoperative fluid infusion in regard to hemodynamic control.…”
Section: Fluid Administrationmentioning
confidence: 99%
“…Early fundamental data do not support the concept of clinically significant hypovolemia associated with pheochromocytoma (35)(36)(37). Plasma volume was determined in 15 patients with pheochromocytoma before any therapy and in ten of these patients after hypotensive drug administration or adrenalectomy, by using human albumin labeled with 125 I (35).…”
Section: Fluid Administrationmentioning
confidence: 99%
“…Two possible markers for hypovolemia are the diameter of the inferior vena cava (IVC) and the thickness of the left ventricle (2)(3)(4)(5)(6)(7). These measurements could be utilized not only in the hospital setting but also in the pre-hospital and military settings to better triage patients and direct resuscitations in austere environments.…”
Section: Introductionmentioning
confidence: 99%